Effects of Palm Leaf Ash and Palm Kernel Fibre on Properties of Compressed Laterite Earth Brick - Jude, K.; Igwe, C. O.; Mohammed, B. M. (Journal of Sustainability and Environmental Management, 2022)
This study was designed to compare the effects of the properties of compressed laterite earth brick (CLEB) stabilized with palm leaf ash (PKA) and palm kernel fiber (KPF). The study was carried out in Building Technology Department, Federal Polytechnic Bida, Niger State. Bricks of 222×110×70 were produced using manual pressed machine where nine bricks each were stabilized with palm kernel fiber for 1%, 2%, and 3%. Also 9 bricks each were stabilized with palm leaf ash for each percent 5%, 10% and 15%. The materials used were Palm Kernel Fiber, Palm Leaf Ash laterite soil, and water. The abrasion resistance test and water penetration test were carried out. The findings revealed that the water penetration rate for the CLEB bricks stabilized with PKF recorded average penetration rate of 10.18 at 1%, 11.52 at 2% and 12.19 at 3%. Only 3% produced higher penetration rate while CLEB stabilized with PLA recorded average water penetration rate of 11.58 at 5%, 10.63 at 10%, and 11.27 at 15%. All were in conformity with NBRRI specification of 12.5%. The abrasion resistance of the 28 day CLEB stabilized with PKF recorded average abrasion of 1.40 at 1%, 1.28 at 2% and 3.68 at 3%. All result were conformity with the NBBRI specification of 6.9. While the abrasion resistance of the 28 day CLEB stabilized with PLA recorded average abrasion of 2.39 at 5%, 2.22 at 10% and 2.32 at 15% which were in conformity with the NBBRI specification of 6.9. Based on the findings of the study, it was concluded that the CLEB stabilized with palm kernel fiber at 1% and 2% are in conformity with NBRRI specification of compressive strength, water absorption rate and abrasion resistance. While compressed laterite bricks stabilized with palm leaf ash should be improve to conform to NBRRI specification.